FUNCTIONALIZATION OF BLOCK COPOLYMERS COMPRISING POLYACRYLAMIDE AND POLY(ETHYLENE OXIDE) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
The application of micelle-type polymeric nanocontainers is considered as one of the most perspective ways to solve the problem of a targeted delivery of toxic and poorly soluble drugs into certain cells of living organisms. Asymmetric micelle forming triblock copolymers (TBC) comprising polyacrylamide (PAAm) and polyetylenoxide (PEO) have hydrophobic complex "core" formed by the hydrogen-bonded PEO/PAAm chains and hydrophilic "corona" of the surplus segments of longer PAAm blocks.  They can bind colloid particles, organic substances and different ions in water solutions. The influence of the anticancer agent doxorubicin on the micellization process of mentioned TBC due to its interaction with the copolymer micelles opened new prospects for using such copolymers as nanocontainers for toxic and poorly soluble drugs. For the successful implementation of mentioned TBC for a drug delivery, they have to contain special ligands or vectors (saccharides, peptides, proteins or antibodies. Such vectors can recognize corresponding receptors on a cellular surface, interact with them, and penetrate into the intracellular space by the endocytosis pathway. In order to introduce the necessary vectors into TBC, corona forming PAA blocks have to contain active groups. In this aspect the methods of TBC functionalization are particularly important. Reactions of polymer analogous modification are well known, comparatively simple and reliable method of functional groups transformation. In the present work the polymer- analogous conversion of triblock copolymers (TBC) PAAm-b-PEO-b-PAAm by the aminomethylation reaction in PAAm blocks under the effect of dimethylamine and formaldehyde (Mannich's reaction) was studied. Kinetic investigations of the Mannich's reaction in TBC as compared to that in pure PAAm were performed by potentiometric titration. It was established that products of copolymers and PAAm aminometilation posess the properties of polyampholits. The existence of two competitive polymer-analogous transformations in PAAm chains such as aminomethylation and alkaline hydrolysis of amide groups was established and discussed.
Keywords: block copolymers, polyacrylamide, polyethylenoxide, aminomethylation, potentiometric titration.